A review of Abd al-Haq al-Marini's services to Moroccan literature: A case study of jihad poetry [In Arabic] - Khaled Al-Touzani (International E-Research Foundation (Bonyan Pouya Pajooh Andisheh Institute), 2021)
The present study tries to show some of the efforts of the Moroccan historian and writer, Dr. Abdel Haq Al-Marini, in Moroccan literature by reading one of his works. The book "Jihad Poetry in Moroccan Literature from the Time of Prince Youssef bin Tashfin al-Murabi to the time of Sultan Mawlawi Abdul Rahman bin Hisham Al-Alawi" is the title of a doctoral dissertation on Moroccan literature from Sidi Mohammed bin Abdullah University in Fez, written in 1989 under the supervision of Dr. Abbas Al-Jarari. Finally, it was published in 1996 by the Ministry of Endowments and Islamic Affairs. In this book, he presents his views on the process of creativity in the poetry of Jihad and how to transfer it intellectually to a poetic goal, and this shows the spirit of patriotism and the history of the struggles of a nation. The distinguishing feature of this type of literature from other literary categories lies in its message and content. This means that the works in the field of resistance literature are often a mirror of the pain and oppression of the people who have fallen victim to authoritarian regimes. These works, while inducing hope in the future and promising the promised victory, call for struggle and resistance against oppression, praise of freedom and liberty, respect for the homeland and the martyrs of the homeland in their hearts.